SKENARIO MASA TANAM KAPAS UNTUK MENEKAN RISIKO KEKERINGAN : STUDI KASUS KABUPATEN JENEPONTO PROVINSI SULAWESI SELATAN(COTTON PLANTING PERIOD SCENARIO FOR MINIMIZING DROUGHT RISK : CASE STUDY JENEPONTO DISTRICT, SOUTH SULAWESI PROVINCE … - P. Redjekiningrum; Y. Apriyana; K.S. Haryanti (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2007)
Water stress is a very important limiting factor for cotton cultivation in Jeneponto District, South Sulawesi Provine. Therefore, it is necessary to optimize water resources. One alternative is to obtain potency of water resources using soil-climate-crop simulation model to calculate ETR/ETM ratio (water satisfaction index). ETR/ETM ratio describing efficiency of water used by the plant. Based on the ratio, scenario of proper planting period can be predicted to minimize drought risk. Based on this idea, an experiment was conducted to mapping of planting periods and water used to enhance the expansion of cotton plantation. The results of research show that potential planting period for Bangkala and West Bangkala districts start from the 3rd dekad of September until the 1st dekad of January, while the best period is on the 1st dekad of November. Potential of planting period for Bontoramba and Turatea districts starts from the 3rd dekad of September until the 1st dekad of May, while the best period is on the 3rd dekad of November. In addition, the appropriate planting period for Batang, Kelara, and Rumbia districts start from the 3rd dekad of September until the 3rd dekad of April, while the best period is on the 1st dekad of December. Requirement for supplementary irrigation for 140 days after planting is about 180-304 mm. However, common necessity of cotton supplementary irrigation for 1-35 day is about 25 – 51 mm, while that is during flowering and fruiting (35 -60 day after planting), ripening (60-105 day after planting), and ripening (105-140 day after planting), are about 40-62, 115-135, 0-68 mm, respectively. It is concluded, deficit and surplus of water for less than 60 dap is not significantly influence plant production, but that is for 60 – 105 day after planting significantly reduces yield of the plant.